NEGARA, KORPORASI DAN GERAKAN PERLAWANAN PETANI ATAS PERAMPASAN TANAH - Totona, Saiful; Sitepu, Badikenita br.; Agustiani, Yurita Puji (Istek Widuri Jakarta, 2025)
This article examines the peasant resistance movement against land dispossession carried out by corporations with state support in Galela, North Maluku. This case study integrates the theory of regimes of dispossession with Smelser’s theory of social movements. The findings indicate that land dispossession by corporations and the state, conducted through intimidation, repression, deception, and the criminalization of peasants with the involvement of security forces, has resulted in unequal land control or ownership, loss of access, shifts in livelihoods, and tensions that have fueled the emergence of a peasant resistance movement. The resistance can be considered successful, as peasants regained access to agricultural land. Moving forward, the Galela Peasant Union or Serikat Petani Galela (SPG) needs to intensify efforts to foster solidarity among peasants through various empowerment initiatives, building collective awareness to ensure the sustainability of the movement in the face of ongoing change and tension.